Edges of the financial imagination - Amin Samman; Martijn Konings (Finance and Society, 2023)
Neither external nor internal to finance, the financial imagination marks out a space where the theoretical and practical aspects of finance come together in the inner life of the subject. That means there is something about financial subjectivity that escapes a functional view on the imagination. The purpose of this forum is to probe the contours of the financial imagination in terms of its perimeters and blind spots, its fantasies and delusions.
Keywords: 300; cultures of capitalism; financial imagination; financial subjectivity; libidinal economy; psychoanalysis